Transformasi Etika Lingkungan Terapan Analisis Manajemen Madrasah Berbasis Nilai-Nilai Al-Qur’an Dan Hadis - Za’far Siddik, Rasyid; Athoillah Yusuf, Ibnu; Yuliany, Yuliany; Haerunisa, Salwa (Hawari: Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
The modern ecological crisis demands a transformation in education that is not only theoretical but also applicable and value-based. This study aims to analyze the internalization of Qur'anic and Hadith values in environmental preservation efforts at MA Al-Ikhlas Paninggaran. Using a descriptive qualitative approach, this research explores how sacred texts are transformed into "Applied Environmental Ethics" through the management functions of planning, organizing, actuating, and controlling. The results indicate that MA Al-Ikhlas Paninggaran has successfully integrated the principles of khalifah fil ardh and the prohibition of israf (over-exploitation) into strategic policies, such as greening programs based on sedekah jariyah and waste management based on thaharah. Uniquely, the monitoring system in this madrasah transcends bureaucratic control by implementing an "Ecological Muhasabah" mechanism, which builds students' spiritual awareness (muraqabah) to protect nature as a form of worship. This study concludes that the synergy between revealed values and local wisdom effectively shapes "eco-piety" in students, while positioning the madrasah as a pioneer in sustainable ecosystem preservation at the local level.